IDDF2019-ABS-0130 Global smoking trends in inflammatory bowel disease: a systematic review of inception cohorts. (7th June 2019) - Sze Wai Li, Venice; Thomas, Tom; Chandan, Joht; Lai, Cheuk Yin; Tang, Whitney; Bhala, Neeraj; Kaplan, Gilaad; Ng, Siew Chien; Ghosh, Subrata
Abstract : Background: The effect of smoking on inflammatory bowel diseases (IBD) may be heterogeneous across ethnicity and geography. This is a systematic review of smoking prevalence across global IBD cohorts. Methods: A systematic literature search was conducted on Medline and Embase from January 1st, 1946 to April 5th, 2018 to identify population-based studies assessing the prevalence of smoking at diagnosis in inception cohorts of Crohn's disease (CD) or ulcerative colitis (UC). Studies that did not report smoking data from the time of diagnosis or the year of IBD diagnosis were excluded . Prevalence of smoking in IBD was stratified by geography and across time. Results: We identified 56 studies that were eligible for inclusion. Never-smokers in the newly diagnosed CD population in the West has increased over the last two decades, especially in the United Kingdom and Sweden; +26.6% and +11.2% respectively. Never-smokers at CD diagnosis in newly industrialised nations have decreased over the 1990s and 2000s; China (-19.36%). Never-smokers at UC diagnosis also decreased in China; -15.4%. The former-smoker population at UC diagnosis in China is expanding; 11%(1990–2006) to 34%(2011–2013). Conclusions: There has been a reduction in the prevalence of smoking in the IBD cohort in the West. This is not consistent globally. Although smoking prevalence has decreased in the general population of newly industrialised nations, this remains an important risk factor with longer-term outcomes awaiting translation in both UC and CD.